Assessoria e consultoria em Serviço Social : o ensino e o exercício profissional em debate - Ozelame, Géssica Cristina (2018)
The present study deals with the advisory and consulting processes, discussing the teaching and the professional practice of social workers, considering that these processes are private assignments and professional competences, however, they are spaces little occupied by the professional category, in which the production of the knowledge manifests itself in an incipient way. Aiming to answer how the advisory and consulting processes are being operationalized in the training and professional practice of social workers in Rio Grande do Sul, the objective was to analyze the aspects related to the training and professional practice of social workers in the advisory and discussing challenges and possibilities. This is a qualitative study, guided by the dialectical-critical method, based on documental, bibliographical and empirical research, totalizing a sample of twenty-three (23) documents for documentary research, thirty-two (32) research productions and twenty-five (25) subjects participating in the empirical research (coordinators, teachers and students of the Bachelor's degree in Social Work). For the treatment and analysis of the data, the content analysis based on Pagés (2006) was used. It is concluded that there are contradictions in the recognition of the importance of teaching the advisory and consulting processes now being denied, sometimes being placed in the background, during training, as well as in the way in which it is being addressed by UFAS. This reality reflects and may explain the incipient manifestation of professional practice in these processes. From the data, it is pointed out the importance of the work of social workers in these processes, and the subjects surveyed stressed the need for Social Work to reorganize itself to expand its work in these spaces, to strengthen the formation process and the materialization of the ethical- political, since these processes are in line with it. Finally, propositions are presented to contribute to overcoming the limits and materialization of the possibilities of acting in these processes.